2017
DOI: 10.1002/cta.2375
|View full text |Cite
|
Sign up to set email alerts
|

Monotonic, critical monotonic, and nearly monotonic low‐pass filters designed by using the parity relation for Jacobi polynomials

Abstract: A new class of continuous-time low-pass filter using a set of Jacobi polynomials, with all transmission zeros at infinity, is described. The Jacobi polynomial has been adapted by using the parity relation for Jacobi polynomials in order to be used as a filter approximating function. The resulting class of polynomials is referred to as a pseudo Jacobi polynomials, because they are not orthogonal. The obtained magnitude response of these filters is more general than the magnitude response of the classical ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…If α = −0.5 and β increases, the ripples in the passband decrease smoothly to be unequal and smaller in magnitude. For β > 1.5 the passband response is nearly monotonic [7], but the rejection slope factor is much steeper than a Butterworth filter cutoff slope. On the other hand, for −1 < β < −0.5 the passband ripples are unequal, but in magnitude are larger than 1.…”
Section: Results Of Approximationmentioning
confidence: 98%
See 1 more Smart Citation
“…If α = −0.5 and β increases, the ripples in the passband decrease smoothly to be unequal and smaller in magnitude. For β > 1.5 the passband response is nearly monotonic [7], but the rejection slope factor is much steeper than a Butterworth filter cutoff slope. On the other hand, for −1 < β < −0.5 the passband ripples are unequal, but in magnitude are larger than 1.…”
Section: Results Of Approximationmentioning
confidence: 98%
“…The characteristic function, used for the proposed analog filter design, can be either n-the degree modified Jacobi polynomial [7] or a chained-function formed as the product of ν lower degree modified Jacobi polynomials, called modified Jacobi seed functions. Thus, a new family of characteristic, or generating, functions of the same degree n, called modified Jacobi chained-function (mJCF), is given by…”
Section: Filter Transfer Functionmentioning
confidence: 99%
“…Introduction: In the recently published paper [1], the authors have reported that the modified Jacobi polynomials can be used to construct a useful allpole lowpass filter functions. For the given lowpass filter degree, two parameters of the modified Jacobi polynomial can be used to a trade-off between passband magnitude response having ripples or being nearly monotonic, transition band width, or group delay deviation in the passband [2].…”
mentioning
confidence: 99%
“…Orthogonal polynomials [6], [39] play an important role in a number mathematical areas. On one hand, orthogonal polynomials have been extensively used in applications for solving practical problems, such as in signal processing [32] and in filter design [38], [30]. On the other hand, the zeros of a certain family of orthogonal polynomials can be interpreted as the electrostatic energy for a system of a finite number of charges; see [43].…”
mentioning
confidence: 99%